Dosimetric comparison of intensity-modulated proton therapy and proton arc therapy for pediatric ependymoma - Helge Henjum; Karoline Mo Feten; Erlend Hartvigsen; Kristian S. Ytre-Hauge; Camilla G. Boer; Camilla H. Stokkevåg (Acta Oncologica)
Background and purpose: Proton Arc Therapy (PAT) is an emerging proton therapy treatment modality with the potential to reduce radiation exposure to healthy tissues compared to conventional Intensity-Modulated Proton Therapy (IMPT) with fewer beams. This is an attractive option for treating pediatric patients, who are vulnerable to radiation-induced side effects. There is, however, a need to investigate the redistribution of dose to the target volume and organs at risk. In this study, we therefore explored the potential of PAT in proton therapy of pediatric ependymoma.